Status of Ambient Particulate Matter and Black Carbon Concentrations in Rajshahi Air, Bangladesh - Begum, Bilkis A; Ahmed, K Shahin; Sarkar, M; Islam, JB; Rahman, AKM Lutfor (Journal of Bangladesh Academy of Sciences, 2015)
Air borne particulate matter (PM) samples (both PM10 and PM2.5) were collected simultaneously from continuous air quality monitoring station (CAMS) at Rajshahi city from December 2012 to February 2013 using two Air Metrics MiniVol samplers. The samples were analyzed for mass and black carbon (BC) concentrations. The present results were compared with the data set during December 2001 to February 2002. It was found that the mean PM10, PM2.5 and BC concentrations have increased 3.3, 6.1 and 3.4 times, respectively than in December 2001 to February 2002 period. Similarly, the ratio of PM2.5/PM10 has increased twice than the previous cited time. In case of BC/PM2.5 ratio, value becomes more than half than the previous period. Hence, PM2.5 concentration has increased tremendously and due to the implementation of policies especially on motor vehicles, BC concentration does not increase linearly as PM2.5. The present data have showed that about 78% of PM10 is PM2.5 whereas in 2001-2002, PM2.5 was only 38% of PM10. The high PM2.5 at Rajshahi city might be due to both local effect and long-range transport. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 147-155, 2015